2023
DOI: 10.3389/fgene.2023.1291719
|View full text |Cite
|
Sign up to set email alerts
|

Clinical feature and genetic analysis of HMBS gene in Chinese patients with acute intermittent porphyria: a systematic review

Yi Ren,
Shuang Li,
Jia-Jia Lei
et al.

Abstract: Background: Early detection and diagnosis are important crucial to prevent life-threatening acute attacks in patients with acute intermittent porphyria (AIP). We aim to provide comprehensive data on the clinical and hydroxymethylbilane synthase (HMBS) gene variant characteristics and genotype-phenotype association of Chinese patients with AIP in order to improve clinicians’ knowledge of AIP and reduce misdiagnosis and mistaken treatment.Methods: We searched the literature on Chinese patients with AIP in PubMed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…A study from China revealed that c.673C> T was the most common mutation and that the c.517C> T mutation was the next most common mutation. 5 Small deletions at c.730_731 is also reported from UK, Italy and Japan. 6,7 Prompt diagnosis in cases presenting as seizures is important as anti-seizure medications like phenytoin and phenobarbitone can induce ALA synthase and can precipitate quadriparesis and respiratory weakness.…”
mentioning
confidence: 91%
“…A study from China revealed that c.673C> T was the most common mutation and that the c.517C> T mutation was the next most common mutation. 5 Small deletions at c.730_731 is also reported from UK, Italy and Japan. 6,7 Prompt diagnosis in cases presenting as seizures is important as anti-seizure medications like phenytoin and phenobarbitone can induce ALA synthase and can precipitate quadriparesis and respiratory weakness.…”
mentioning
confidence: 91%